A Synthetic Biology Workflow Reveals Variation in Processing and Solubility of Nitrogenase Proteins Targeted to Plant Mitochondria, and Differing Tolerance of Targeting Sequences in a Bacterial Nitrogenase Assay - Okada, Shoko; Gregg, Christina M.; Allen, Robert Silas; Menon, Amratha; Hussain, Dawar; Gillespie, Vanessa; Johnston, Ema; Byrne, Keren; Colgrave, Michelle Lisa; Wood, Craig C. (Frontiers in Plant Science, 2020)
While industrial nitrogen fertilizer is intrinsic to modern agriculture, it is expensive and environmentally harmful. One approach to reduce fertilizer usage is to engineer the bacterial nitrogenase enzyme complex within plant mitochondria, a location that may support enzyme function. Our current strategy involves fusing a mitochondrial targeting peptide (MTP) to nitrogenase (Nif) proteins, enabling their import to the mitochondrial matrix. However, the process of import modifies the N-terminus of each Nif protein and may impact nitrogenase assembly and function. Here we present our workflow assessing the mitochondrial processing, solubility and relative abundance of 16 Klebsiella oxytoca Nif proteins targeted to the mitochondrial matrix in Nicotiana benthamiana leaf. We found that processing and abundance of MTP::Nif proteins varied considerably, despite using the same constitutive promoter and MTP across all Nif proteins tested. Assessment of the solubility for all MTP::Nif proteins when targeted to plant mitochondria found NifF, M, N, S, U, W, X, Y and Z were soluble, while NifB, E, H, J, K, Q and V were mostly insoluble. The functional consequence of the N-terminal modifications required for mitochondrial targeting of Nif proteins was tested using a bacterial nitrogenase assay. With the exception of NifM, the Nif proteins generally tolerated the N-terminal extension. Proteomic analysis of Nif proteins expressed in bacteria found that the relative abundance of NifM with an N-terminal extension was increased ~50-fold, while that of the other Nif proteins was not influenced by the N-terminal extension. Based on the solubility, processing and functional assessments, our workflow identified that K. oxytoca NifF, N, S, U, W, Y and Z successfully met these criteria. For the remaining Nif proteins, their limitations will need to be addressed before proceeding towards assembly of a complete set of plant-ready Nif proteins for reconstituting nitrogenase in plant mitochondria.